1996
DOI: 10.1083/jcb.132.6.1079
|View full text |Cite
|
Sign up to set email alerts
|

Identification, localization, and functional implications of an abundant nematode annexin.

Abstract: Abstract. Cultures of the nematode C. elegans were examined for the presence of calcium-dependent, phospholipid-binding proteins of the annexin class. A single protein of apparent mass on SDS-polyacrylamide gels of 32 kD was isolated from soluble extracts of nematode cultures on the basis of its ability to bind to phospholipids in a calcium-dependent manner. After verification of the protein as an annexin by peptide sequencing, an antiserum to the protein was prepared and used to isolate a corresponding cDNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…Lipocortins (annexins) are a family of at least 18 structurally related cytoplasmic proteins in mammals, which exhibit Ca 2ϩ -dependent binding to phospholipids (35,36). These proteins are widely distributed in eukaryotic cells and are characterized by a similar structure, with four or eight repeats of a 70-amino acid conserved core, and differ by a variable N-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…Lipocortins (annexins) are a family of at least 18 structurally related cytoplasmic proteins in mammals, which exhibit Ca 2ϩ -dependent binding to phospholipids (35,36). These proteins are widely distributed in eukaryotic cells and are characterized by a similar structure, with four or eight repeats of a 70-amino acid conserved core, and differ by a variable N-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…While nex-1 and nex-3 are expressed continuously in the developmental stages of C. elegans, the expression of nex-2 and nex-4 was reported to be only temporal [32]. The highest expressed member of this protein family, nex-1, is present in many structures in the worm [33]. Ultrastructural studies of nex-1 showed it to be localized to the spermathecal valve, a structure that represents the final gate for the egg on its passage from the ovary to the spermathecal chamber.…”
Section: Annexins In Nematodes: the Free-living Caenorhabditis Eleganmentioning
confidence: 99%
“…Annexins have been found in many species of eukaryotes, including Xenopus (22), Drosophila melanogaster (23), Dictyostelium (11), Caenorhabditis elegans (8), Neurospora (1), Giardia (15), zebrafish (13), and all of the plant types (9) so far examined. Structurally annexins can be characterized as having a core of either four or eight conserved domains, each containing about 70 amino acids.…”
Section: Infectious Pancreatic Necrosis Virus (Ipnv) Is a Member Of Tmentioning
confidence: 99%